Full Mouth Rehabilitation of a Worn Out Dentition using Multidisciplinary Approach - Chidambaram, Ramasamy; Grover, Manita; Veeravalli, Padmanabhan Thallam (Journal of Orofacial Research, 2013)
Restoration of a badly mutilated dentition has been a challenge to a dentist’s skills and capabilities. Principles of occlusion have to be applied keeping the esthetic factor in mind to improve the psychological aspect of the patient and his social acceptance. A combination of mechanical, biological and esthetic factors is mandatory for occlusal rehabilitation. This clinical report describes the prosthodontic management of a 46-year-old male patient with attrition of natural dentition.